Effect of protective cultures on spoilage bacteria and the quality of vacuum-packaged lamb meat. (December 2022) - Xu, Michelle M.; Kaur, Mandeep; Pillidge, Christopher J.; Torley, Peter J.
Abstract: Protective cultures, as natural antimicrobials, have the ability to suppress the growth of spoilage bacteria and can potentially be used to extend the shelf-life of fresh meat and help reduce food waste. As there have been limited reports on the application of this approach in fresh red meat, the aim of this study was to evaluate the potential and practicality of this approach for red meat shelf-life extension based on the antimicrobial efficacy and quality impact of selected protective cultures. Two protective cultures (one containing Lactobacillus sakei and the other containing Staphylococcus carnosus and L. sakei ) were applied to chill-stored (4 °C) vacuum-packaged lamb meat to determine their effects on spoilage bacteria as well as non-microbiological meat quality over a 20-day storage period. These protective cultures dominated the microbiota throughout storage and effectively suppressed the growth of common meat spoilage bacteria, Brochothrix thermosphacta, Pseudomonas spp., and Enterobacteriaceae . Meat color (measured in CIE L*a*b* color space) changed slightly in culture-treated samples in the later stage of storage, but the changes were not unacceptable based on previously reported thresholds for consumer acceptability. The mixed culture containing additional S. carnosus exhibited a slightly stronger inhibitory effect against the spoilage bacteria but also caused more changes in meat color. Protective culture addition did not significantly affect meat pH, texture, or microstructure. Overall, these results demonstrated the potential of biopreservation using protective cultures for fresh red meat shelf-life extension. Graphical abstract: Image 1 Highlights: Protective cultures suppressed the growth of spoilage bacteria throughout storage. Protective cultures dominated the microbial communities on treated samples. Protective cultures caused slight but acceptable changes in meat color. Protective cultures did not affect meat pH, texture, or microstructure.